Key Mechanisms of Risk Management in South Africa’s National Government Departments: The Public Sector Risk Management Framework and the King III Benchmark - Tankiso Moloi (Central European Public Administration Review)
Government provides essential services to the population and therefore, uncertainties that could hinder government’s objectives should be identified, mitigated/controlled and monitored. Using the content analysis for data extraction in the annual reports of national government departments (NGDs), this paper explored risk management practices in South Africa’s public service, with national government departments as a case in point. The findings are that in general, there are poor risk management practices in the NGDs as the majority of the observed categories were not disclosed in the NGDs annual reports. Since risk deals with the uncertainties on the objectives, it is concerning that NGDs have poor risk management practices, particularly because they are enablers (implementers) of government overarching strategy. As enablers of government strategy, it is recommended that NGDs view risk management as a process that enables them to identify threats which could hinder the attainment of their objectives, whilst also leveraging opportunities that may arise. It is further recommended that the risk process is viewed as a scenario or option analysis exercise that allows NGDs to properly plan, understand the intended outcomes and prepare responses to deal with any uncertainties. A summarised and harmonized risk governance requirement used for the purpose of exploring risk management disclosures has been suggested by this study and it could be used as a reference point of risk disclosure improvement by NGDs.